Respuesta :

kixrrx

Answer:

A. x2 + x – 4

Step-by-step explanation:

I took the assignment on Edgeniuty 2020.

For a function f(x) = x2 + 1  and g(x) = 5 – x the value of (f + g)(x) is as follows:

(f + g)(x) = x² - x + 6

f(x) = x² + 1

g(x) = 5 - x

Therefore,

Function

A function relates input and output. f(x) and g(x) are ways to represent function. Therefore, f(x) = x² + 1 shows that the function f takes x and sum x squared and 1.

The function g also takes the difference of 5 and x.

(f + g)(x)  = f(x) + g(x)

Therefore,

(f + g)(x) = x² + 1 + 5 - x

(f + g)(x) = x² - x + 6

learn more on function here: https://brainly.com/question/8653864

ACCESS MORE